Why Do Political Parties Change their Policy Positions? A Review. (November 2016) - Fagerholm, Andreas
This article summarises the rapidly increasing number of studies dealing with parties' positional changes. After a short introduction and a brief discussion of a number of elementary deﬁnitions and delimitations, the second section evaluates eight factors commonly associated with party policy change. Here, the proposition that parties tend to respond systematically to changes in public opinion seems to be the most studied and, similarly, the most supported explanation. The third and ﬁnal section identiﬁes a number of research gaps and recommends topics for future research.